2011
DOI: 10.1093/rheumatology/ker230
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated HS6ST2 in osteoarthritis and Kashin-Beck disease inhibits cell viability and influences expression of the genes relevant to aggrecan metabolism of human chondrocytes

Abstract: HS6ST2 in the reverse subtraction library was identified as a down-regulated gene in OA and KBD at both mRNA and protein levels. The percentage of safranion O staining area was correlated positively with the percentage of HS6ST2-positive chondrocytes in OA and KBD cartilage. After HS6ST2-specific short interfering RNA (siRNA) transfection to C28/I2 cells, the cell viability was inhibited significantly, and the mRNA expression levels of SOX9 and AGC1 were reduced markedly, while MMP3 expression was increased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…However, there was sGAG staining in the other zones of articular cartilage, suggesting the association of PG loss with cell death during KBD onset in children. In contrast, the depletion of sGAG was observed in the surface and middle zone of articular cartilage from adult KBD patients, similar to that seen in osteoarthritic patients [2, 10]. Therefore, it is now believed that KBD pathology in adults is more like sub-type of OA with a rare aetiology [11] because their pathological and metabolic changes in articular cartilage are quite similar to those observed in OA patients, although some differences in gene expression profiles have been recently reported [12].…”
Section: Proteoglycan Catabolism In Kbdmentioning
confidence: 54%
See 1 more Smart Citation
“…However, there was sGAG staining in the other zones of articular cartilage, suggesting the association of PG loss with cell death during KBD onset in children. In contrast, the depletion of sGAG was observed in the surface and middle zone of articular cartilage from adult KBD patients, similar to that seen in osteoarthritic patients [2, 10]. Therefore, it is now believed that KBD pathology in adults is more like sub-type of OA with a rare aetiology [11] because their pathological and metabolic changes in articular cartilage are quite similar to those observed in OA patients, although some differences in gene expression profiles have been recently reported [12].…”
Section: Proteoglycan Catabolism In Kbdmentioning
confidence: 54%
“…Interestingly, a distinct difference in the loss of PGs from the different zones of articular cartilage was seen between juvenile and adult patients [2, 9, 10]. In the juvenile KBD patients, loss of sulphated GAG (sGAG) staining in articular cartilage was mainly localised to areas within the deep zone where chondrocyte necrosis was observed [2, 9].…”
Section: Proteoglycan Catabolism In Kbdmentioning
confidence: 99%
“…Aside from cancer, HS6ST2 has also been reported to be involved in embryonic stem cell differentiation (28) and idiopathic pulmonary fibrosis (29). In our previous study, we demonstrated that both the mRNA and protein levels of HS6ST2 were significantly downregulated in the cartilage of patients with osteoarthritis or Kashin-Beck disease (23). In particular, the silencing of HS6ST2 reduced cell viability and altered the expression of cartilage-related genes.…”
Section: Discussionmentioning
confidence: 84%
“…However, the role of HS6ST2 in chondrocyte growth and differentiation is not yet fully understood. In our previous study, we reported that HS6ST2 expression was significantly decreased in the cartilage of patients suffering from osteoarthritis and Kashin-Beck disease and was associated with cell proliferation and Acan metabolism in chondrocytes (23). These data suggest that HS6ST2 is involved in regulating chondrocyte growth.…”
Section: Introductionmentioning
confidence: 78%
“…In a previous study at our department, differentially expressed genes (DEGs) in OA cartilage were screened by suppression subtractive hybridization (SSH). SFMBT2 was identified from the reverse subtraction library by sequence analysis and a similarity search with the BLAST programme . We selected this gene for further investigations in this study.…”
Section: Resultsmentioning
confidence: 99%